Odpowiedzi

2009-10-18T09:12:04+02:00
10(x-y)-4(1-x)/ 3 = y /*3
{
7 + x-3y/4 = 2x- 4+5/ 3 /*12

10(x-y)-4(1-x)=3y
{
7 + 3x-9y = 2x- 36

10x-10y-4+4x=3y
{
3x-2x=-36-7+9y

14x-13y=4
{
x=-43+9y

x=-43+9y
{
14(-43+9y) -13y =4

x=-43+9y
{
-602+126y-13y=4

x=-43+9y
{
113y=606 /:113

x=-43+9y
{
y=5 41/113

x=-43+ 45 369/113
{
y=5 41/113

x=-43 + 48 30/113
{
y=5 41/113

x=5 30/113
{
y=5 41/113




2x - 1/5 + 3y-2/4 = 2
{
- 3x + 1/5 - 3y + 2/4 = 0
________________________
x =2

x=2
{
2x - 1/5 + 3y -2/4 =2 /*10
x=2
{
20x -2 + 30y -5 = 20

x=2
{
40-2-5-20=-30y

x=2
{
13=-30y

x=2
{
30y=-13 /30

x=2
{
y=- 13/30

Proszę bardzo :)